(untitled) (Fiep Bulletin - online, 2016)
The physical and psychological stress of modern life has become a public health problem. It is observed that most people complain of muscle pain and physical exhaustion. We note also that the people are looking for methods such as massage therapy to improve the quality of life and sense of well-being. Due lack of time of modern life, techniques that promote physical and psychological well-being and can be performed in a short time as the Quick Massage and Podal Massage are having more and more followers. Thus, this study investigates the improvement of well-being and decreased of stress base doesn’t he result of physiological and psychological effects of Quick Massage and Podal Massage done together. In this study were measured blood pressure and heart rate before and after performing the massages by beauticians in 30 spontaneous volunteers. It was found that there was a reduction in blood pressure and heart rate, because the touch massage and maneuvers such as slip, promoted wide spread relaxation. The volunteers also completed a questionnaire indicating their stress levels before and after the massage and it was found that 97% of those had the feeling of relaxation or much relaxation.